A new earthworm species of the genus Amynthas (Clitellata: Megascolecidae) from northern Taiwan, false synonymy between Amynthas corticis (Kinberg, 1867) and Amynthas sheni (Chen, 1935) and other taxonomic issues relating to A. corticis - Shen, Huei-Ping; Chang, Chih-Han (Zootaxa, 2025)
This study describes a new species of earthworms belonging to the genus Amynthas (Clitellata: Megascolecidae) from northern Taiwan. It is named Amynthas popi sp. nov. It is a large earthworm with four pairs of spermathecal pores in 5/6–8/9. It has a postsetal papilla medial to each male porophore and papillae closely or widely paired in presetal VIII, widely paired in postsetal XIX, and occasionally more closely paired in presetal XIX. Its compact prostate glands together with short, stout and horizontal prostatic ducts are rarely seen among the native Amynthas earthworms known from Taiwan. Amynthas sheni (Chen, 1935) is a false synonym of Amynthas corticis (Kinberg, 1867) as the former has postsetal papillae on ventrum of VIII and occasionally also on IX, four pairs of esophageal hearts in X–XIII, well-developed prostate glands in XVI–XXI and long, U-curved prostatic ducts, which clearly set it apart from the latter. Other taxonomic issues relating to A. corticis are discussed. Additionally, Amynthas jampeanus fumigatus (Michaelsen, 1899) should be regarded as a subspecies of Amynthas bonthainensis (Benham, 1896) since it bears a very close resemblance to A. bonthainensis than to Amynthas jampeanus (Benham, 1896). The following combination is proposed: Amynthas bonthainensis fumigatus (Michaelsen, 1899) comb. nov.